2022
DOI: 10.1186/s12877-022-03059-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophile-to-lymphocyte ratio (NLR) and lactate dehydrogenase (LDH) levels for geriatric patients with COVID-19

Abstract: Aim In this study it was aimed to evaluate the prognostic factors for the geriatric patients with confirmed COVID-19 in a tertiary-care hospital at Kastamonu region of Turkey. Method Patients (≥65-year-old) who had PCR positivity for COVID-19 between March 2020 and April 2020 in our center were recorded retrospectively. A p value less than 0.05 was considered significant. Ethical committee approval was given from the Bolu University with decision n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…As it was expected [30,31] , there was highly significant correlation between plasma levels of CRP and AAT from COVID-19 patients (Fig 2A). Lower levels PaO2/FiO2 were negatively correlated with elevated levels of LDH which was reported previously as an indication of mortality rate [32,33] (Fig 2B). Consistent with previous reports, we also observed Higher levels of LDH in non-survivors compared with survivors (411.3±160.2, and 345.1±131.3, respectively) (Fig.…”
Section: Correlations Among Plasma Profiles In the Sars-cov2 Patientssupporting
confidence: 83%
“…As it was expected [30,31] , there was highly significant correlation between plasma levels of CRP and AAT from COVID-19 patients (Fig 2A). Lower levels PaO2/FiO2 were negatively correlated with elevated levels of LDH which was reported previously as an indication of mortality rate [32,33] (Fig 2B). Consistent with previous reports, we also observed Higher levels of LDH in non-survivors compared with survivors (411.3±160.2, and 345.1±131.3, respectively) (Fig.…”
Section: Correlations Among Plasma Profiles In the Sars-cov2 Patientssupporting
confidence: 83%
“…In severe cases of COVID-19, viral attachment to lymphocytes, damage by inflammatory cytokines, migration, and aggregation to lung tissue are the causes of persistent decline in peripheral blood lymphocytes [ 31 ]. Decreased peripheral blood lymphocyte counts in COVID-19 patients have been widely reported as a risk factor for severe disease [ 9 , 13 , 31 ]. Our study showed that the effect of COVID-19 on lymphocytes was not attenuated on day 8, indicating that lymphopenia could be a major factor in predicting poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have also focused on novel biomarkers, such as soluble urokinase receptors and C-reactive protein isoforms [ 10 , 11 ]. Clinical prediction tools combining these easily measurable but nonspecific laboratory markers have also been proposed [ 12 , 13 ]. Although they are useful in estimating the risk of resistance to treatment and mortality in COVID-19 patients, most are evaluated only during the initial visit or on admission.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil-lymphocyte ratio (NLR) is a systemic inflammatory marker used as a determinant of the diagnosis as well as prognosis of patients with a viral or bacterial infection. [13][14][15] Previous study has shown the importance of leukocyte kinetics, which is represented as NLR, in the first 3-5 days after hyperinflammation occurred. 13 "As a result, when compared to other inflammatory markers such as Procalcitonin and C-Reactive Protein, NLR proved to be a more rapid, feasible, cost-effective, and affordable marker that could be easily performed in any healthcare facility setting.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study defined certain COV of NLR in COVID-19 patients but was dedicated to prognostic, disease severity, and mortality markers. 14,22,40 Therefore, the COV of NLR showed the other value to determine the occurrence of SPBI. A high prevalence ratio of NLR was also observed, indicating that a high NLR above the COV during the first three days is likely to suggest the presence of bacterial infection.…”
mentioning
confidence: 99%